Skrining Fitokimia Dan Aktivitas Antioksidan Ekstrak Etanol Pelepah Daun Terubuk (Saccharum spontaneum var. edulis (Hassk) K. Schum.) - shofia aulia; Eko Sri Wahyuningsih; Neni Sri Gunarti (Jurnal Buana Farma, 2023)
Utilization of terubuk leaves effectively can increase the food value of the food waste. This influenced researchers to determine the content of secondary metabolites and antioxidant activity in terubuk leaves. The purpose of this study was to identify the ethanol content of terubuk leaves through phytochemical screening and TLC analysis and to determine the antioxidant activity of terubuk leaves. This research method uses quantitative methods namely Identification of compounds by phytochemical screening, followed by chromatographic identification Thin Layer (TLC) and qualitative testing of antioxidant activity with the method DPPH (1,1-diphenyl-2-fikrihidrazyl) was measured using a Uv-Visible spectrophotometer with various concentrations of 25, 50, 75, 100, and 125 μg/mL. The results of the phytochemical screening showed that the ethanol extract of the leaves was positive for alkaloids, flavonoids, saponins, tannins, quinones, monoterpenoids and sesquiterpenoids. Thin Layer Chromatography (TLC) results were positive for Flavonoids, Alkaloids, Quinones, Tannins.The results of antioxidant research using μg/mL the ethanol extract of terubuk leaves have activity as antioxidants. The intensity of antioxidant activity of terubuk leaves was 180.148 ± 0,898 μg/mL so that from the results of this study terubuk leaves had moderate potential antioxidant activity against DPPH free radicals. Terubuk leaf ethanol extract contains secondary metabolites and has antioxidant activity.